Antiurolithiatic efficacy of combination preparations of Dolichos biflorus and Crataeva nurvala: folk medicines used in Indian traditional medicine - Swati Kaushik; Manjusha Choudhary; Shami Rajpal (SpringerOpen, 2021)
Abstract Background In spite of advances in the modern allopathic medicines, there is no satisfactory treatment of kidney stones, so formation and growth of calculi continues to trouble mankind. In India, many herbal formulations are in use for the treatment of urolithiasis. The purpose of the present study was to investigate the antiurolithiatic efficacy of combined extract of plants Dolichos biflorus (D.b) (hydroalcoholic seed extract) and Crataeva nurvala (C.n) (aqueous bark extract) in ethylene glycol-induced urolithiasis in Wistar rats. Rats were divided into 4 groups. Ethylene glycol (0.75% v/v, p.o.) was administered for 35 days. Different drug treatments were given from the 21st to 35th day of the study. On the last day, rats were sacrificed, and different samples were taken for further analysis. Results Both the combination drug treatments were found to be effective in treating urolithiasis. More significant protection was observed on treatment with the fraction ratio of D.b + C.n (3:1). Histopathology analysis showed degenerated glomeruli and inflammatory cells in urolithiasis control. The same were regenerated on treatment with combined extract of the two plants. Conclusion Administration of the combined plant extracts in a ratio of D.b + C.n (3:1) possesses better efficacy against ethylene glycol-induced urolithiasis in rats which may be evaluated further for mechanistic pathway elucidation in vivo.